The organizational powers of (digital) media. (September 2019) - Beverungen, Armin; Beyes, Timon; Conrad, Lisa
Digital media are pervasive, ubiquitous and mundane constituents of organization. Organized life relies on, and is propelled by, technologies that store, transmit and process data and are based on networked computation. How can we understand and explore the fundamental mediatedness of organization? This article contextualizes and introduces the special issue on 'The organizational powers of (digital) media' by staging an encounter between organization theory and media theory. In provoking investigations of the power and effects of technological mediation in its many guises, not least in regard to digital or computational media, this encounter ushers in a 'medial thought' of organization.